2018
DOI: 10.2139/ssrn.3156942
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differentiation in Intergenerational Care-Giving and Migration Choices

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…We speculate that young adults’ tight-knit relationships with grandparents may have been influenced by their own parents’ tight-knit relationships with those grandparents. In other words, it is possible that young adults as children witnessed their parents caring for their older grandparents making the former more likely to support their parents—the so-called demonstration effect of modeling desired behavior to one’s children (Stark & Cukrowska-Torzewska, 2018). We recommend that future studies address the transmission of intergenerational solidarity from grandparent–parent dyads to parent–grandchild dyads over the family life course (Hank et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that young adults’ tight-knit relationships with grandparents may have been influenced by their own parents’ tight-knit relationships with those grandparents. In other words, it is possible that young adults as children witnessed their parents caring for their older grandparents making the former more likely to support their parents—the so-called demonstration effect of modeling desired behavior to one’s children (Stark & Cukrowska-Torzewska, 2018). We recommend that future studies address the transmission of intergenerational solidarity from grandparent–parent dyads to parent–grandchild dyads over the family life course (Hank et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When the need for regular help becomes substantial, it may also trigger geographical rapprochement between family members (Smits et al , 2010). Many studies found that adult children and ageing parents choose to co-reside, settle down or relocate to live in close vicinity of each other in order to facilitate the provision of help (Rogerson et al , 1997; Mulder, 2007; Pettersson and Malmberg, 2009; Heylen et al , 2012; Seltzer and Friedman, 2014; Stark and Cukrowska-Torzewska, 2018). By analogy, the availability of local persons willing to help encourages residence at a distance or even the undertaking of migration, as in the case of Romanian young adults, who appeared to be more likely to move abroad when they had a sibling living in the parental household or in its close proximity (Zimmer et al , 2013).…”
Section: Availability Of Children Non-family Support and The European...mentioning
confidence: 99%
“…Across countries, families are using their own unpaid labor, especially that of women, to provide care for older family members (Stark 2005). Unpaid care for older men is often provided by spouses, while for women it is provided by other family members, especially by daughters, as documented for the Republic of Korea (Yoon 2014), the People's Republic of China (Chen et al 2018), and Western Europe (Stark and Cukrowska-Torzewska 2018). One outcome is lower hospitalization rates for elderly people living with family members compared to the elderly who live alone, an outcome observed in Mexico (González-González et al 2011).…”
Section: Introductionmentioning
confidence: 99%